PERAN ORANG TUA SEBAGAI PENDIDIK SPIRITUAL ANAK DI LINGKUNGAN KELUARGA BERDASARKAN KITAB ULANGAN PASAL ENAM - Agus Joko Manteus; Sara Wahyuni (Sekolah Tinggi Teologi Injili Indonesia Bali, 2023)
God gives a mandate to parents to educate their children to know and love God. Parents as leaders in the family who carry out God's commandments become the first and foremost educators for their children. Forms of education given by parents through oral teaching and exemplary life through real deeds. Every parent is obliged to educate their children from the womb. Childhood is an important period in instilling an integral education. Parents must realize that what happens in the family has a big impact on personality development, faith development and ultimately the development of children's spiritual intelligence. By using a qualitative research approach, to obtain a comprehensive study. The process of children's education must always be built within the framework of Christ's forgiving and redemptive grace, through the work of the Holy Spirit. The application of a biblical pattern of child education is only effective when it is applied to those who have experienced fellowship in Christ.